Intervention based on functional analytic psychotherapy in a case of panic disorder with agoraphobia (Revista Brasileña de Terapia Comportamental y Cognitiva, 2012)
Therapeutic strategies described as effective for anxiety disorders include behavioral and cognitive-behavioral procedures of exposure and coping of aversive situations. However, considering that the behavioral pattern common in anxiety disorders is the phobic avoidance, the application of these strategies may difficult the adhesion or promote escape and avoidance of the therapeutic process. The Functional Analytic Psychotherapy is an alternative for dealing with these avoidance/escape behaviors and it can promote coping responses. This case report describes an analysis of the therapeutic relationship of a client with Panic Disorder and Agoraphobia. The intervention based on FAP was considered to help dealing with the avoidance behavior in the therapeutic process. Results show the efficacy of the procedures adopted and confirm the possibility of using FAP for improving the effectiveness of the empirically based psychotherapies.